Ice seals as sentinels for algal toxin presence in the Pacific Arctic and subarctic marine ecosystems - Alicia M. Hendrix; Kathi A. Lefebvre; Lori Quakenbush; Anna Bryan; Raphaela Stimmelmayr; Gay Sheffield; Gabriel Wisswaesser; Maryjean L. Willis; Emily K. Bowers; Preston Kendrick; Elizabeth Frame; Thomas Burbacher; et al. (Marine Mammal Science, 2021)
Domoic acid (DA) and saxitoxin (STX)‐producing algae are present in Alaskan seas, presenting exposure risks to marine mammals that may be increasing due to climate change. To investigate potential increases in exposure risks to four pagophilic ice seal species ( Erignathus barbatus , bearded seals; Pusa hispida , ringed seals; Phoca largha , spotted seals; and Histriophoca fasciata , ribbon seals), this study analyzed samples from 998 seals harvested for subsistence purposes in western and northern Alaska during 2005–2019 for DA and STX. Both toxins were detected in bearded, ringed, and spotted seals, though no clinical signs of acute neurotoxicity were reported in harvested seals. Bearded seals had the highest prevalence of each toxin, followed by ringed seals. Bearded seal stomach content samples from the Bering Sea showed a significant increase in DA prevalence with time (logistic regression, p = .004). These findings are consistent with predicted northward expansion of DA‐producing algae. A comparison of paired samples taken from the stomachs and colons of 15 seals found that colon content consistently had higher concentrations of both toxins. Collectively, these results suggest that ice seals, particularly bearded seals (benthic foraging specialists), are suitable sentinels for monitoring HAB prevalence in the Pacific Arctic and subarctic.

Domoic acid in milk of free living California marine mammals indicates lactational exposure occurs - Lauren Rust; Frances Gulland; Elizabeth Frame; Kathi Lefebvre (Marine Mammal Science, 2014)

New Insights into the Controls and Mechanisms of Plankton Productivity in Coastal Upwelling Waters of the Northern California Current System - Raphael Kudela; Neil Banas; John Barth; Elizabeth Frame; David Jay; John Largier; Evelyn Lessard; Tawnya Peterson; Andrea Vander Woude (Oceanography, 2008)